Predicting the potential geographical distribution of mango, an important tropical economic tree species, under current and climate change based on Maxent model - Yi, Sangui; Huang, Yuanhe; Liu, Zongling; Zhu, Zhengjie; Su, Hongxin (Frontiers in Plant Science, 2025)
IntroductionMango is a major tropical economic tree species in China, along with being a vital source of livelihood for farmers and an important maintainer of ecosystem services in southern China. Identifying the potential suitable habitats for mango under current and future climate scenarios, along with key influencing factors, can inform mango plantation. However, little is known about these.MethodsUsing Maxent, we modeled the current and future potential suitable habitats for mango, evaluated the impact of environmental variables on their distribution, and identified shifts related to climate change in their distribution.ResultsThe results showed that the current potential suitable habitats for mango were primarily located in southern China, within the tropical and subtropical regions. Under climate scenarios of both SSP585 and SSP126, the potential suitable habitats not only encompassed the southern provinces of China that were already covered but also expanded northward to include central provinces, particularly Sichuan and Chongqing municipalities. Mango exhibited a clear tendency to migrate toward higher altitudes and latitudes under SSP585 scenario, whereas the trend of mango migration to such areas was less pronounced under SSP126 scenario. Mean Temperature of Coldest Quarter, Annual accumulated temperature (≥10°C), Precipitation of Coldest Quarter, and UV-B Seasonality were identified as the main factors shaping the distribution of the potential suitable habitats for mango.DiscussionOur recommendation to adapt to climate change is to expand mango cultivation to high-latitude/altitude areas, particularly Sichuan-Chongqing in central China, along with water-saving irrigation, shade management, development of drought- and disease-resistant cultivars, and mapping of the potential suitable habitats for different varieties.